Musculoskeletal Health, Kidney and Liver Function in Retired Jockeys - Cullen, S.; Donohoe, A.; McGoldrick, A.; McCaffrey, N.; Davenport, C.; Byrne, B.; Donaghy, C.; Tormey, W.; Smith, D.; Warrington, G. (International Journal of Sports Medicine, 2015)
The long-term implications of making-weight daily on musculoskeletal health and functioning of the kidney and liver remain unknown. This study aimed to investigate musculoskeletal health and kidney and liver function in a group of retired jockeys. 28 retired male jockeys (age 50–70 years) provided fasting blood samples for markers of bone metabolism and kidney and liver function. A dual-energy x-ray absorptiometry (DXA) scan was performed for the assessment of bone mineral density (BMD). Established reference ranges were used for interpretation of results. Comparisons were made between retired jockeys based on the professional racing licence held: Flat, National Hunt or Dual. Mean whole-body osteopenia was reported, with no differences between groups. Bone markers, micronutrients, electrolytes and associated hormones, and markers for kidney and liver function were within clinical normative ranges. No differences existed between groups. Results indicate the retired jockeys in this study do not demonstrate compromised bone health or kidney and liver function. However, the retired jockeys may not have undergone chronic weight cycling in the extreme manner evident in present-day jockeys, indicating the next generation of jockeys may face more of a problem. Jockeys should be tracked longitudinally throughout their racing career and beyond.
Keywords: jockey; horse-racing; weight category athletes; making-weight; bone health; renal function